MULAT SARIRA: SEBUAH KONTEMPLASI DALAM KONSTRUKSI KESADARAN SPIRITUAL - Gusti Ngurah Yoga Semadi Semadi; Putu Sabda Jayendra Jayendra; I Nengah Artawan Artawan (WIDYANATYA, 2023)
Abstract Human certainly want something that can be subject to self-awareness. In order for humans to be submissive with awareness, of course, mental processing is needed. This inner exercise is a process towards being creative. Humans are born should be able to create an inner condition by having an attitude that is always grateful for the gifts and abundance of His love. The point is that humans can be as they are to always be able to prostrate and be grateful is itself an awareness. This awareness must always be nurtured so that it can be stable in facing the realities of life. Through asceticism that is always introspective and self-introspective (mulat sarira) which will eventually reach a spiritual level of awareness. This is the path of seeking inwardly, by always holding on to dharma (truth). All of us should be able to forgive each other and share information towards self-transformation. The goal is for all human beings to experience inner and outer happiness. However, in the current situation, people always speculate about teaching and guiding mankind through religious doctrines. Actually, practical life is needed through a simple way of life, but having and being able to develop brilliant thoughts and see the world with its various different phenomena as one unit from big family (vasudeva kutumbakam). Keywords: Mulat Sarira, Self-Introspection, Vasudeva kutumbakam